MUDHARABAH FINANCING IN ISLAMIC BANKS: IMPLEMENTATION AND ITS CONTRIBUTION TO THE OBJECTIVES OF ISLAMIC ECONOMICS - Waluyo, Bambang (Universitas Airlangga, 2016)
This study discusses the implementation of mudharabah in Islamic banks. The purpose of this study is to analyze the implementation of mudharabah in Islamic bank financing products. This study provides food for thought on shifting financing in Islamic banks towards financing that is more in line with the objectives of Islamic economics. The research uses an exploratory descriptive qualitative approach. The research is library research conducted exploratively. Data collection is through literature and documentation surveys. Analysis uses qualitative data analysis. Interpretation and conclusion drawing are done by connecting the data obtained in the literature and documentation surveys. The results of the study show that the objective of Islamic banks should be to become institutions that introduce Islamic economic objectives. Islamic banking institutions should uphold social objectives and promote Islamic values to their staff, customers, and the general public, including contributing to the social welfare of the community, promoting sustainable development projects, and reducing poverty. The most appropriate product developed by Islamic banks in line with Islamic economic objectives is mudharabah-based financing. Although there are challenges in its implementation, in mudharabah there are two agreements that can be made to overcome them: (i) The mudharib is required to contribute capital. (ii) The mudharib is required to share in losses up to a certain limit. Keywords: mudharabah, financing, Islamic economic objectives